2017
DOI: 10.1186/s40813-017-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Delaying pigs from the normal production flow is associated with health problems and poorer performance

Abstract: BackgroundDelaying pigs from advancing through the production stages could have a negative impact on their health and performance. The objective of this study was to investigate the possible implications of delaying pigs from the normal production flow on pig health and performance in a farrow-to-finish commercial farm with a self-declared All-In/All-Out (AIAO) management.ResultsThree flows of pigs were defined, flow 1 (i.e. pigs that followed the normal production flow; 8 weeks in the nursery stage, 4 weeks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 12 publications
2
44
0
Order By: Relevance
“…Birth [ 1 , 2 , 36 ] and weaning weight [ 3 – 6 , 36 ] have been identified as predictors of post-weaning growth. Although, piglets born light (< 1.00 kg) have a higher mortality rate [ 8 ], a higher feed conversion ratio [ 13 ] and need more time to reach market weight [ 24 ], one should discriminate between piglets that have been born light for gestational age e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Birth [ 1 , 2 , 36 ] and weaning weight [ 3 – 6 , 36 ] have been identified as predictors of post-weaning growth. Although, piglets born light (< 1.00 kg) have a higher mortality rate [ 8 ], a higher feed conversion ratio [ 13 ] and need more time to reach market weight [ 24 ], one should discriminate between piglets that have been born light for gestational age e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Slow growing pigs are more at risk to be delayed in all-in-all-out systems, resulting in remixing, increasing the potential for disease transmission, but most importantly contributing to considerable production losses (e.g. costs of feed, labour and penalties at slaughter) [ 1 ]. However, it has been suggested that some pigs born light may have the potential to compensate during suckling [ 2 ] and subsequent growth stages [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early cross-fostering was performed on piglets coming from larger litters with similar birth weights as non-cross fostered pigs and no negative effects on carcass yield were observed. Late cross-fostering was performed in low birth weight piglets; however, such small piglets are likely to continue to grow at a slower rate ( 42 44 ). It is unclear what role early cross-fostering plays in the development of ear lesions; however, our results suggest that there is some association, albeit likely an indirect link.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly lower number of weaned piglets in comparison to TNB and NBA in young sows may be due to several factors, including inadequately developed maternal instinct (GÄDE et al, 2008). CALDERÓN DIAZ et al (2017) report that lower values of reproductive traits may be caused by inappropriate management conditions, e.g. stress before and during farrowing, lower birth weight, inappropriate care of piglets at the time of weaning, sow milk yield, and housing hygiene.…”
Section: Discussionmentioning
confidence: 99%